The Effect Of Problem-Solving Learning Methods On The Accuracy Of Underhand Passes In Girls' Volleyball At SMP N 2 Hamparan Perak Deli Serdang - Jualina Widyawaty; Jenas Pardomuan Sihotang; Jepni Piola Togatorop; Iwan Julius Gulo; Jhon Ferinando Tarigan (Journal Physical Health Recreation (JPHR), 2025)
The influence of problem-solving learning methods on the accuracy of underhand passing in women's volleyball is the driving force of this research. SMPN 1 Pulau Merbau, Teluk Ketapang Village, Pulau Merbau District. Students have not shown their greatest potential in Underhand Passing, therefore errors often occur in that part of the test. This research is a Quasi-Experimental research, with the title "The Influence of Problem Solving Learning Style Learning Techniques on the Accuracy of Underhand Passing in Women's Volleyball." SMPN 2 Hamparan Perak Deli Serdang In 2025, the population in this study were all 102 Female Volleyball Players of SMPN 2 Hamparan Perak Deli Serdang. The sample taken was 15 female students. The instrument for arm muscle explosive power used the Underhand Passing test along with the Underhand Passing accuracy test. After that, the data was processed statistically, for the normality test with the Liliefors test at a significance level of 0.05. The hypothesis proposed is the Influence of the Problem Solving Learning Style Learning Method on the Accuracy of Underhand Passing in Girls' Volleyball at SMPN 2 Hamparan Perak Deli Serdang. Based on the processed data, it can be concluded that there is an Influence of the Problem Solving Learning Style Learning Method on the Accuracy of Underhand Passing in Girls' Volleyball at SMPN 2 Hamparan Perak Deli Serdang, where the initial test with an average of 41.87 in the pre-test increased by 3.6 to 45.47 in the post-test with the results (t count 12.345> t table 1.72)